Три поросенка: сказка / С. В. Михалков ; худ. М. Рудаченко - Михалков Сергей Владимирович (Самовар 1990, 2002)
Экземпляры: б/ф-8 (20140319) / Инвентарный номер: 34185 / Цена: 30.00 / Авт.знак: М 69 / ББК: Д